'In the North you can't be openly gay': Contextualising sexual practices among sexually and gender diverse persons in Northern Canada. Issue 12 (2nd December 2018) - Logie, Carmen H.; Lys, Candice L.; Schott, Nicole; Dias, Lisa; Zouboules, Makenzie R.; Mackay, Kayley
ABSTRACT: Scant research has addressed health and well-being among lesbian, gay, bisexual, transgender, and queer (LGBTQ) persons in the Arctic. The Northwest Territories (NWT) has among Canada's highest rates of sexually transmitted infections (STIs). LGBTQ persons in NWT are at the nexus of LGBTQ and Arctic health disparities. Yet little is known of their sexual health needs. This qualitative study explored the sexual health needs of LGBTQ persons in the NWT. We conducted semi-structured, in-depth interviews with 51 participants, including 16 LGBTQ youth aged 15–24, 21 LGBTQ adults aged 25 and above, and 14 key informants who worked with LGBTQ persons. Social-ecological approaches to understanding sexual health guided this study. Participants discussed how structural contexts such as heteronormativity in sexual health education and a lack of access to safer sex tools constrained their ability to practice safer sex. Social contexts of intersectional stigma resulted in shame, concealing identities, and fear of accessing safer sex materials. Myriad factors influenced partner communication about safer sex practices, including honesty, consent, and relationship power. Findings suggest the need for comprehensive sexuality education and interventions that address syndemics of substance use, stigma, and low self-esteem to advance sexual health among LGBTQ persons in Northern Canada.